2021
DOI: 10.1007/s00277-021-04539-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic assessment for chronic myelomonocytic leukemia in the context of the World Health Organization 2016 proposal: a multicenter study of 280 patients

Abstract: Knowledge on chronic myelomonocytic leukemia (CMML) patients from Argentina and Brazil is limited. Our series of 280 patients depicted an older age at diagnosis (median 72 years old), 26% of aberrant karyotypes, and a prevalence of myelodysplastic (60%) and CMML-0 subtypes (56%). The median overall survival (OS) was 48.2 months for patients in CMML-0 (Ref.), 24.7 months for those in CMML-1 (HR = 2.0, p = 0.001), and 8.8 months for patients in CMML-2 (HR = 4.6, p < 0.001). In the CMML-0 category, median OS were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although attempts have been made to identify factors predicting survival in CMML, the prognostic value of factors remains inconsistent and controversial. Adès et al reported that peripheral WBC > 13 × 10 9 /L was associated with worse OS in CMML patients treated with AZA [ 36 ].In a large cohort of retrospective multicenter study including 280 CMML patients from Latin American, González et al revealed that Hb ≥ 8- < 10 g/dL, Hb < 8 g/dL, poor karyotypes, WHO 2016-CMML-1, and CMML-2 were independent adverse clinical factors associated with poor survival of CMML [ 11 ]. In the present study, clinical and laboratory factors, such as aberrant karyotype, FAB or WHO classification, peripheral hemoglobin < 80 g/L, and platelets < 100 × 10 9 /L were not correlated to the survival of patients, which may partially relate to the limited sample size in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although attempts have been made to identify factors predicting survival in CMML, the prognostic value of factors remains inconsistent and controversial. Adès et al reported that peripheral WBC > 13 × 10 9 /L was associated with worse OS in CMML patients treated with AZA [ 36 ].In a large cohort of retrospective multicenter study including 280 CMML patients from Latin American, González et al revealed that Hb ≥ 8- < 10 g/dL, Hb < 8 g/dL, poor karyotypes, WHO 2016-CMML-1, and CMML-2 were independent adverse clinical factors associated with poor survival of CMML [ 11 ]. In the present study, clinical and laboratory factors, such as aberrant karyotype, FAB or WHO classification, peripheral hemoglobin < 80 g/L, and platelets < 100 × 10 9 /L were not correlated to the survival of patients, which may partially relate to the limited sample size in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CMML is a rare disease with an incidence of 0.3 per 100 000 in western counties [6][7][8][9][10]. It typically occurs in the elderly with a median age at diagnosis of 72-76 years and a male:female ratio of (1.5-3):1 [6,7,[11][12][13].The prognosis of this aggressive myeloid malignancy is poor with a median survival of only 12 to 29 months and a 14-29% risk of acute leukemic transformation [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%